Grain boundary mediated hydriding phase transformations in individual polycrystalline metal nanoparticles. Issue 1 (December 2017) - Alekseeva, Svetlana; Fanta, Alice; Iandolo, Beniamino; Antosiewicz, Tomasz; Nugroho, Ferry; Wagner, Jakob; Burrows, Andrew; Zhdanov, Vladimir; Langhammer, Christoph
Abstract Grain boundaries separate crystallites in solids and influence material properties, as widely documented for bulk materials. In nanomaterials, however, investigations of grain boundaries are very challenging and just beginning. Here, we report the systematic mapping of the role of grain boundaries in the hydrogenation phase transformation in individual Pd nanoparticles. Employing multichannel single-particle plasmonic nanospectroscopy, we observe large variation in particle-specific hydride-formation pressure, which is absent in hydride decomposition. Transmission Kikuchi diffraction suggests direct correlation between length and type of grain boundaries and hydride-formation pressure. This correlation is consistent with tensile lattice strain induced by hydrogen localized near grain boundaries as the dominant factor controlling the phase transition during hydrogen absorption. In contrast, such correlation is absent for hydride decomposition, suggesting a different phase-transition pathway. In a wider context, our experimental setup represents a powerful platform to unravel microstructure–function correlations at the individual-nanoparticle level. Grain boundaries are thought to significantly mediate phase transformations in nanoparticles. Here, the authors combine multichannel plasmonic nanospectroscopy and transmission Kikuchi diffraction to study the role of grain boundaries in hydriding reactions of Pd nanoparticles on a single-particle level.